The Role Of Islamic Religious Education Teachers In Shaping Students' Leadership Values At State Junior High School 21 Bengkulu City - Hidayat, Wahyu; Sundari, Siti (Universitas Dehasen Bengkulu, 2024)
This study aims to analyse the role of Islamic Religious Education (PAI) teachers in shaping students' leadership values in Sekolah Menengah Pertama (SMP) Negeri 21 in Bengkulu City. Leadership is one of the important values that need to be developed in students to prepare them to become individuals who are able to contribute positively in society. PAI teachers have a strategic role in this process, as leadership values can be taught and internalised through religious teachings. The research method used was a qualitative method with a descriptive approach. Data were collected through in-depth interviews with PAI teachers, classroom observation, and analysis of related documents. Data were analysed thematically to identify the role of PAI teachers in shaping students' leadership values. The results showed that PAI teachers at SMP Negeri 21 Bengkulu City have a significant role in shaping students' leadership values through several strategies. First, they integrate leadership values in PAI subject matter. Second, they become leadership role models for students through their daily attitudes and behaviours. Third, they facilitate extracurricular activities that support students' leadership development, such as student organisations and religious activities. This study concluded that the role of PAI teachers is very important in shaping students' leadership values at SMP Negeri 21 Bengkulu City. PAI teachers not only teach leadership theory, but also provide real examples and create an environment that supports students' leadership development. The recommendation from this study is for schools and the government to strengthen training and support for PAI teachers in an effort to develop student leadership effectively.